Dynamics of zander Stizostedion Lucioperca (L.) abundance in the Ural-Caspian region under present conditions - N. N. Popov; A. I. Kushnarenko (Юг России: экология, развитие, 2015)
The impact of ecological, trophic and anthropogenic factors on biological characteristics of zander is shown. Specific features of water regime in the Ural River that limit zander abundance are determined.